Impact of budget variance on donor funding in NGOs: case study on “Stichting BRAC International” - Iftekhar, Rokaiya (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.